2022
DOI: 10.1161/strokeaha.121.032608
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of Vascular Brain Health: Insights From Ex Vivo Magnetic Resonance Imaging–Histopathology Studies in Cerebral Small Vessel Disease

Abstract: Sporadic cerebral small vessel disease (SVD) is a major contributor to vascular cognitive impairment and dementia in the aging human brain. On neuropathology, sporadic SVD is characterized by abnormalities to the small vessels of the brain predominantly in the form of cerebral amyloid angiopathy and arteriolosclerosis. These pathologies frequently coexist with Alzheimer disease changes, such as plaques and tangles, in a single brain. Conversely, during life, magnetic resonance imaging (MRI) only captures the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 111 publications
0
29
0
Order By: Relevance
“…Nevertheless, the same review showed increased MRI‐assessed white matter hyperintensity (WMH) burden in individuals with DLB compared to cognitively unremarkable participants, which was consistently supported by neuropathological data. An ongoing challenge is that although WMH is considered a marker of cerebrovascular disease, other etiologies, including AD‐associated pathology and axonal loss, may associate with WMH 63–65 …”
Section: Neuropathology and Prevalence Of Co‐pathologiesmentioning
confidence: 99%
“…Nevertheless, the same review showed increased MRI‐assessed white matter hyperintensity (WMH) burden in individuals with DLB compared to cognitively unremarkable participants, which was consistently supported by neuropathological data. An ongoing challenge is that although WMH is considered a marker of cerebrovascular disease, other etiologies, including AD‐associated pathology and axonal loss, may associate with WMH 63–65 …”
Section: Neuropathology and Prevalence Of Co‐pathologiesmentioning
confidence: 99%
“…Moreover, undetermined-SMICH inclined to have a greater presence of severe BG EPVS. Based on existing evidence, BG EPVS and deep CMB are associated with HTN-SVD, whereas CSO EPVS are associated with CAA ( Greenberg et al, 2009 ; Charidimou et al, 2013 , 2017 ; van Veluw et al, 2022 ). Thus, severe hypertensive arteriosclerosis may be the primary denominator of SMICH patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Enlarged perivascular spaces (EPVS) in the centrum semiovale (CSO) and exclusively cortical cerebral microbleeds (CMBs) are consistently associated with CAA. In contrast, EPVS in the basal ganglia (BG) and deep CMBs presumably account for hypertensive angiopathy ( Greenberg et al, 2009 ; Charidimou et al, 2013 , 2017 ; van Veluw et al, 2022 ). Previous studies noted that there was a higher burden of total CMBs among SMICH patients; ( Stemer et al, 2010 ; Chen et al, 2016 ) however, the number of CMBs stratified by different locations (deep vs. lobar) had not been evaluated, and the phenotypes of other cerebral small vessel disease (SVD) MRI markers remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…With the present approach, the analysis of individual blood distribution and 3D angiographies to detect which main trunks and segments really become "vasospastic'" in the patient's timeline and how that correlate in (i) perfusion studies and (ii) final brain outcome [3,16,90] in the machine learning (ML) analysis becomes feasible. The contents of (i) early ischemic brain areas and (ii) perihematomal edema areas could be studied in detail with ex vivo MRI combined with histopathology [36,103] in aSAH patients who succumbed during their neurointensive care. It remains to be seen how salvable these "penumbral" areas become with novel therapies [32,53,77,96].…”
Section: Suggested Further Research and Development-aneurysmal Sahmentioning
confidence: 99%